The Relationship Between Depression Levels and Spiritual Levels in Breast Cancer Patients in General Hospital in Bali, Indonesia - Putri Ariani, Ni Ketut; Sutrisna, I Putu Belly; Silaen , Rebecca Mutia Agustina; Yosef, Herman; Narayana Manjunatha (Faculty of Medicine, Universitas Airlangga, 2026)
Introduction: Breast cancer is the most common cancer. In Bali, among 3020 cancer cases from 2017 to 2019 in women, breast cancer accounted as most common for 15% of cases. Good spiritual well-being is considered a protective factor against suicidal ideation and the severity of depression or other mental disorders, where patients with high spirituality can overcome depression and manage stress better. Methods: This research is a descriptive observational study using a cross-sectional design aimed at examining the correlation between levels of depression and spiritual well-being in breast cancer patients at the hospital. The level of depression was measured with Beck Depression Inventory (BDI). Spiritual level was measured using the Spiritual Well-Being Scale (SWBS). Results: A total of 40 participants from breast cancer patients were included in this study. Most breast cancer patients had moderate (57.5%) to high (42.5%) levels of spirituality, with none reporting low spirituality. Nearly half (47.5%) showed no signs of depression, while 45% experienced mild depression and 7.5% had moderate depression. No patients had severe depression. Study found higher spirituality associated with lower average depression scores (p = 0.009), indicating that greater spiritual well-being may help reduce depression in breast cancer patients. Conclusion: This study concludes that higher levels of spirituality are significantly associated with lower levels of depression in breast cancer patients. Spiritual well-being play a protective role in supporting emotional health, suggesting that incorporating spiritual support into patient care may help reduce depression and improve overall mental well-being in individuals facing chronic illness.